Characteristics and Prognostic Factors in Gastric Adenocarcinoma Patients with Distant Metastasis - Hoang, Tien Manh; Hoang, Van Hieu; Bui, Thi Thu Hoai (Asian Pacific Journal of Cancer Biology, 2022)
Objective: To explore the characteristics and prognostic factors of distant metastatic gastric adenocarcinoma (DMGA). Methods: The data of DMGA patients who were enrolled in the SEER database from 2010 to 2017 was obtained. The Chi-squared test was performed for comparison between groups. The Kaplan-Meier method and the log-rank test was used for survival analysis. Univariate and multivariate Cox regression analysis was used to identify independent prognostic factors. Results: A total of 2324 DMGA patients was identified. The association between different metastatic sites and clinicopathological characteristics was detected. The survival curves of patients with single and double-organ metastasis were established. The multivariate Cox analysis indicated that age, histological grade, T stage, N stage, surgery and tumor size were independent prognostic factors. Conclusion: DMGA patients have poor outcomes, especially brain metastasis, bone metastasis, liver-brain metastasis, and lung-brain metastasis. Age <60 years old and cancer-directed surgery indicated a better prognosis, while higher T and N stage, higher grade and tumor size ≥5 cm indicated a worse prognosis.